Effect of natural additives on concrete mechanical properties. Issue 1 (1st January 2021) - Gallegos-Villela, Rocio R.; Larrea-Zambrano, Fabian D.; Goyes-Lopez, Clara E.; Perez-Sanchez, Josue F.; Suarez-Dominguez, Edgardo J.; Palacio-Perez, Arturo
Abstract: The construction industry commonly uses steel-reinforced concrete despite the high levels of pollution in its production process. In this research, it was studied the dossing effect of nopal mucilage and Ixtle fiber as additives for the enhancement of concrete's mechanical properties: compression strength, flexural strength, heat transfer coefficient, ultrasonic pulse rate, ED-XRF, and roughness by fractal dimension analysis. It was found a remarkable improvement in mechanical properties when both natural additives are used. It was observed an increase of potassium and calcium ions concentration after additive dosing. This behavior determines the suitability of the blend for its application in the engineering and construction industry to reduce cement or steel use.